Ambiphilic geometrically constrained phosphenium cation. Issue 50 (4th June 2018) - Volodarsky, Solomon; Dobrovetsky, Roman
Abstract : Geometrically constrained phosphenium cation was synthesized, and in contrast to previously reported phosphenium cations, it is ambiphilic and reactive towards small molecules. Abstract : In this work the synthesis of a geometrically constrained phosphenium cation is shown. In contrast to previously reported phosphenium cations, the geometrical constriction of the P-center in this cation makes it ambiphilic and reactive towards small molecules such as H2 O, ROH and NH3 .